Evaluation of Radiation Safety for Hospital Staff Using Dosimetric Data - Khadka, Narendra; Neupane, Bijay Raj; Amgain, Suman; Koirala, Maha Prasad; Baniya, Smriti; Baniya, Hom Bahadur (Amrit Research Journal, 2024)
Hospitals utilize various manmade radiation sources for therapeutic and sterilization purposes. However, improper monitoring of these sources can lead to radiation leakage, posing potential health risks. At Bir Hospital, data from dosimeters were analysed using appropriate statistical methods. The analysis revealed that the overall absorbed dose is 0.078 mSv per year, well below the 20 mSv annual dose limit recommended by the International Commission on Radiological Protection (ICRP). This indicates that the staff at Bir Hospital are working under safe radiation exposure levels. A Chi-square test further confirmed that there is no significant gender-based variation in radiation dose absorption among the staff. These findings demonstrate that the hospital’s radiation safety measures are effective, ensuring the safety of its employees. This data underscores the importance of maintaining and monitoring radiation safety. To enhance safety standards, it is recommended that all hospitals require medical staff to use dosimeters and provide access to dosimeter data for research and analysis.